Problems of formation of Kazakhstan’s tourist image in the global information space - Кazbayeva М.К.; Saurbayeva Ә.Ж. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2022)
The article deals with the problems of forming the image of the state, its image and functions in the international arena. In the global information society, the process of obtaining and exchanging information has reached a new level. This is the relevance of the work to determine the direction of formation of the international image of the state and the study of ways for its further modernization. The research work includes the content of the concepts of «image», «brand» in the media image of the state, as well as familiarization with their functions. The positive image of the state is formed, first of all, in connection with foreign policy, foreign investment, social stability, internal political processes, national branding. As an effective method, thepromotion of the national brand of Kazakhstan through domestic tourism is determined. During the contentanalysis, materials and expert interviews about the tourism industry of Kazakhstan in the media were analyzed.